Profitability as a Source of Growth and Sustainability in the Business Environment - León Chinchilla, Anabelle (2011)
The profit value constitutes the central axis of the sustainability and growth of a business Because of this, decisions directed towards developing projects ofinvestment to be financed by means of debt, should consider the importance that the generating capacity of incomes generated by the execution of the projects be more than proportional to the finance charge of the resources, due to the fact that both will impact in the utilities and therefore in the performance on the investment. An imbalance in these proportions can carry giddy to the closing of the business, aspect that is intensified in times of contraction of the markets.